JASALMA INTELLEKT – INFORMATIKA MUǴALLIMINIŃ JAŃA OQÍTÍW QURALÍ - Otepbergenov, J.S. (SCIENCE and SOCIETY, 2025)
This article briefly analyzes the implementation of artificial intelligence (AI) in the process of teaching computer science and its significance as a new, practical tool for teachers. AI platforms enhance learning effectiveness through individualization, automatic code analysis, adaptive tests, and assessment, while developing students' practical skills. The article proposes projects within the framework of the «Uzbekistan – 2030» strategy that align with national and local contexts - national content, smart agriculture, and public service interfaces. It also emphasizes the need to maintain data reliability, authenticity, and the teacher's role in AI implementation. Overall, AI is an effective tool that serves not to replace teachers, but to enhance their pedagogical abilities and contribute to the training of modern personnel.